(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Learning to write news texts is a crucial aspect in developing students’ literacy competencies at the junior high school level. This study aims to describe the implementation, obstacles, and steps taken by teachers in the process of teaching news text writing in grade VII of Al-Mahmudiyah Karang Anyar Islamic Junior High School in the 2025/2026 academic year. The approach used was a qualitative case study with observation, interviews, and document analysis methods. Researchers processed the data using several data analysis techniques, namely data verification, data classification, and data interpretation. The results of the study indicate that the learning process is still formal and teacher-oriented, with the main obstacles being a lack of innovation in teaching methods, media used, and direct student experience. Efforts made by teachers include utilizing digital media and contextual approaches to increase student interest and writing skills. Recommendations include increasing teacher creativity, developing learning media, and strengthening a culture of literacy in the school environment. It is hoped that the results of this study can serve as a reference in efforts to improve the quality of news writing learning in junior high schools.